Active Ageing Index, New Emphasis within the same Methodology. The Role of the Internet - Berde, Éva; Kuncz, Izabella (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
Our paper focuses on the role of the Internet in older people’s lives and suggests that the weighting given to Internet usage should be increased when calculating the Active Ageing Index (AAI). We analyse the results of two weighting systems, which differ from the original one created by an expert group. First, we use the coefficients calculated by Djurovic et al. (2017), then create our own system in which the Internet usage component is given a very high coefficient value, ceteris paribus. Evaluations are done for AAI 2010, 2012, 2014, 2016 and 2018. The rank order of countries differs in the alternative weighting systems, but these differences are slight, and decrease year by year, suggesting the robustness of the original weighting system. This also shows that older EU citizens are using the Internet more and more, and that Internet usage is becoming a category similar to basic literacy. Finally, we recommend that AAI include a more sophisticated indicator of Internet usage instead of just asking respondents if they have used the Internet at least once a week in the previous three months.